2015
DOI: 10.18632/oncotarget.3835
|View full text |Cite
|
Sign up to set email alerts
|

MiR-338-3p inhibits epithelial-mesenchymal transition in gastric cancer cells by targeting ZEB2 and MACC1/Met/Akt signaling

Abstract: MicroRNAs (miRNAs) are involved in the epithelial-mesenchymal transition (EMT) process and are associated with metastasis in gastric cancer (GC). MiR-338-3p has been reported to be aberrantly expressed in GC. In the present study, we show that miR-338-3p inhibited the migration and invasion of GC cells in vitro. Knocking down miR-338-3p in GC cells led to mesenchymal-like changes. MiR-338-3p influenced the expression of the EMT-associated proteins by upregulating the epithelial marker E-cadherin and downregula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
86
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(94 citation statements)
references
References 30 publications
8
86
0
Order By: Relevance
“…Furthermore, MACC1 expression was positively correlated with tumor size, grade, invasion of depth, LNM, and TNM stage. Our results were consistent with those of previous studies in GAC [8, 3133] demonstrating that MACC1 should be useful as a clinical candidate biomarker of GAC.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, MACC1 expression was positively correlated with tumor size, grade, invasion of depth, LNM, and TNM stage. Our results were consistent with those of previous studies in GAC [8, 3133] demonstrating that MACC1 should be useful as a clinical candidate biomarker of GAC.…”
Section: Discussionsupporting
confidence: 93%
“…The expression of ZEB2 has been reported in different tumors, including bladder cancer [30,31]. Recent reports highlighted that ZEB2 was closed related to EMT [32,33], suggesting ZEB2 is a key factor in promoting the initiation and development of cancer. It was reported that ZEB2 led to the loss of epithelial marker E-cadherin and disrupt cell-to-cell adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…ZEB2 is the second family member and described as a factor collaborating with the TGF-b signaling pathway by interacting with SMAD factors and promotes tumor cell invasion [16][17][18]. Reports showed that ZEB2 could be regulated by miR-139-5p in HCC which inhibits EMT and metastasis [21], miR-338-3p in gastric cancer cells which inhibits EMT [22], miRNA-200a in HCC suppresses metastatic potential of side population cells [23], miR-132 in lung cancer suppresses the migration and invasion [24] and others [25,26]. In HCC, there are other miRNAs like miR-132 and miR-206 which could inhibit hepatocellular carcinoma cell proliferation, metastasis and promote apoptosis of hepatocellular carcinoma [27,28].…”
Section: Discussionmentioning
confidence: 99%